63: Laryngeal Mask Airway Versus Endotracheal Intubation for Positive Pressure Ventilation with Chest Compressions in Neonatal Porcine Model. Issue 6 (1st June 2014) - Mehrem, A Abou; Graham, R; Srinivasan, G; Heese, R; Dakshinamurti, S
Abstract: BACKGROUND: Endotracheal intubation (EI) is recommended in neonatal resuscitation whenever chest compressions (CC) are indicated. Laryngeal mask airway (LMA) is used effectively to provide positive pressure ventilation (PPV) to newborns after delivery but the efficacy of LMA during PPV with CC is not well studied. OBJECTIVES: To determine if LMA or EI deliver comparable tidal volumes, inspiratory (VTi) and expiratory (VTe), during PPV and CC in neonatal piglets. DESIGN/METHODS: Twenty four- to six-day-old piglets (with weight 1.8 kg to 2.8 kg) were randomized to either EI (size 3.5 cuffed [n=9]) or LMA (size 1.5 [n=11]); mechanically ventilated; anesthetized with ketamine/propofol; and paralyzed with rocuronium. Arterial and venous lines were placed. Respiratory flow and airway pressure were measured continuously using a pneumotach, pressure transducer, and WinDaq acquisition system. Two-minute samples were recorded, and blood gases analyzed during baseline ventilation (BL), PPV with T-piece resuscitator (TP), and PPV with CC (TPCC) at 3:1 ratio. RESULTS: LMA insertion failed in one animal mandating EI. Ten animals were analyzed in each group. At BL there was no significant difference between EI and LMA in VTi, VTe, VT leak, Positive end expiratory pressure (PEEP), ventilator rate, FiO2, PaCO2, or PaO2 . Peak inspiratory pressure (PIP) was significantly higher with LMA; mean difference was 1.6 cm H2 O, and 95% CI (0.12 to 3.1). Respiratory data during TP and TPCC are presented in Table 1 . Comparing TP to TPCC showed that adding CC resulted in higher leak (P<0.05), lower PEEP (P<0.001) and lower PaO2 (P<0.001). Abdominal distension was observed with LMA but not EI, with postmortem gastric air aspirates of 22 to 80 mL. CONCLUSIONS: LMA provided comparable VT to EI during PPV and PPV with CC with slightly higher PIP. EI resulted in lower PaCO2 levels, which was within acceptable limits with both devices. Newer LMAs which allow decompression of the stomach as well as the efficacy of LMA in restoring spontaneous circulation after asphyxia should be investigated.